Production of pro- and anti-inflammatory cytokines by monocytes from patients with paracoccidioidomycosis - Peracoli, MTS; Kurokawa, C. S.; Calvi, S. A.; Mendes, R. P.; Pereira, PCM; Marques, S. A.; Soares, AMVC (Elsevier B.V., 2003)
Monocytes and macrophages can produce a large repertoire of cytokines and participate in the pathogenesis of granulomatous diseases. We investigated the production of pro- and anti-inflammatory cytokines by monocytes from patients with active paracoccidioidomycosis. Peripheral blood monocytes from 37 patients and 29 healthy controls were cultivated with or without 10 mug/ml of lipopolysaccharide (LPS) for 18 h at 37 degreesC, and the cytokine levels were determined in the culture supernatants by enzyme immunoassay. The results showed that the endogenous levels of tumor necrosis factor alpha (TNF-alpha), interleukin-1 beta (IL-1beta), IL-6, IL-8, IL-10 and transforming growth factor beta detected in the supernatant of patient monocytes cultivated without stimulus were significantly higher than those produced by healthy controls. These data demonstrated that monocytes from patients with active paracoccidioidomycosis produce high levels of cytokines with both inflammatory and anti-inflammatory activities. However, patient monocytes produced significantly lower TNF-alpha and IL-6 levels in response to LPS when compared to normal subjects, suggesting an impairment in their capacity to produce these cytokines after LPS stimulation. Concentrations of IL-1beta, IL-8 and IL-10 in cultures stimulated with LPS were higher in patients than in controls. These results suggest that an imbalance in the production of pro- and anti-inflammatory cytokines might be associated with the pathogenesis of paracoccidioidomycosis. (C) 2003 Editions scientifiques et medicales Elsevier SAS. All rights reserved.
Keywords: paracoccidioidomycosis; monocytes; cytokines